Changes of AT2 receptor levels in the rat adrenal cortex and medulla induced by bilateral nephrectomy and its modulation by circulating ANG II - Peters, Barbara; Clausmeyer, Susanne; Teubner, Philipp; Obermüller, Nicholas; Kränzlin, Bettina; Gretz, Norbert; Inagami, Tadashi; Peters, Jörg (Journal of histochemistry & cytochemistry, 2001)
We studied regulation of the AT2 receptor by investigating the effect of bilateral nephrectomy (bNX) in Sprague-Dawley rats. The expression of aldosterone synthase (CYP11B2) and AT2 receptor mRNA was detected by nonradioactive in situ hybridization. AT2 receptor mRNA was detected in cells of the first two or three subcapsular cell layers of the zona glomerulosa (ZG) and in the medulla of sham-operated animals. After bNX, the number and area of distribution of AT2 receptor-positive cells increased in the ZG. This was associated with an enlargement of the steroidogenic active ZG and with reduced proliferation rate (sham 5.9 ± 0.9%; bNX 2.4 ± 0.2%; p > 0.02). Infusion of angiotensin II (ANG II; 200 ng/kg/min SC for 56 hr) to bNX rats did not reverse the effect of nephrectomy on the distribution of AT2 receptor expression, although mRNA levels per cell were reduced compared to NX alone. ANG II infusion decreased proliferation rate further (0.4 ± 0.07%; p > 0.001). In the adrenal medulla after bNX, decreased expression of the AT2 receptor was associated with increased proliferation (2.6 ± 0.2% vs 6.6 ± 0.5%). These results demonstrate differential regulation of the AT2 receptor in the adrenal gland and suggest that expression of the AT2 receptor is involved in regulating proliferation and differentiation in the ZG and medulla., (J Histochem Cytochem 49:649-656, 2001)
Gesehen am 28.06.2022
Die 2 in AT2 im Titel ist tiefgestellt